Automatização e monitoramento do sistema hidráulico de uma instituição de ensino usando a placa de microprocessamento Arduíno e o Software MIT APP Inventor - SOUZA, Jéssica Rodrigues de (2019)
This work appears as a proposal to improve the hydraulic system of an educational establishment, being this system of relevant importance in the structure and maintenance of the establishment, since it aims to minimize problems related to the reduction of the period of class and water contigency. It seeks to improve the e ciency of the existing system through the automation process, using the Arduino microprocessor board, due to its low cost, hardware and software, and compatibility with various devices Such as the Bluetooth module. A communication interface has also been developed through an application development software for the Android operating system, aiming at a simple and user-friendly interface for the monitoring of the system being studied.